Ketamine modulation of the haemodynamic response to spreading depolarization in the gyrencephalic swine brain - Sánchez-Porras, Renán; Santos, Edgar; Schöll, Michael; Kunzmann, Kevin; Stock, Christian; Silos, Humberto; Unterberg, Andreas; Sakowitz, Oliver (Journal of cerebral blood flow & metabolism, 2017)
Spreading depolarization (SD) generates significant alterations in cerebral haemodynamics, which can have detrimental consequences on brain function and integrity. Ketamine has shown an important capacity to modulate SD; however, its impact on SD haemodynamic response is incompletely understood. We investigated the effect of two therapeutic ketamine dosages, a low-dose of 2 mg/kg/h and a high-dose of 4 mg/kg/h, on the haemodynamic response to SD in the gyrencephalic swine brain. Cerebral blood volume, pial arterial diameter and cerebral blood flow were assessed through intrinsic optical signal imaging and laser-Doppler flowmetry. Our findings indicate that frequent SDs caused a persistent increase in the baseline pial arterial diameter, which can lead to a diminished capacity to further dilate. Ketamine infused at a low-dose reduced the hyperemic/vasodilative response to SD; however, it did not alter the subsequent oligemic/vasoconstrictive response. This low-dose did not prevent the baseline diameter increase and the diminished dilative capacity. Only infusion of ketamine at a high-dose suppressed SD and the coupled haemodynamic response. Therefore, the haemodynamic response to SD can be modulated by continuous infusion of ketamine. However, its use in pathological models needs to be explored to corroborate its possible clinical benefit.